Research on Measurement Techniques for Integrated Optical Waveguide-Based Electric Field Sensors - Feng Zhou; Zhenghao Chai; Yinglong Diao; Zhaozhi Long (IEEE Access)
The growing demand for high-precision sensing technologies in power systems has positioned the development of novel electric field measurement tools as a critical metrological challenge. This study presents a broadband photoelectric electric field sensor based on the Mach-Zehnder interference phenomenon in asymmetric straight wave-guides. Furthermore, a three-dimensional electric field measurement system was developed through systematic investigation of multidimensional field measurement methodologies. Experimental results demonstrate that the proposed device achieves broadband electric field measurement with linearity up to 0.9996 and power-frequency measurement accuracy exceeding 97%. The system demonstrates concurrent measurement capability for both lightning impulse waveforms and operational power frequency electric fields. The synthesized three-dimensional measurement error remains below 4%, enabling precise omnidirectional electric field detection.